4-Nerolidylcatechol induces autophagy in human glioblastoma cells - Renato Ramos Massaro; Carla Abdo Brohem; Rebeca Leite de Almeida; Diogo Pineda Rivelli; Juliano Andreoli Miyake; Alison Colquhoun; Silvia Berlanga de Moraes Barros; Silvya Stuchi Maria-Engler (Universidade de São Paulo, 2018)
ABSTRACT Gliomas account for the majority of primary malignant brain tumors and present invasive behavior into adjacent healthy tissue. While 4-NC had previously shown to induce apoptotic cell death in a melanoma model, for the glioma model described in this paper 4-NC is cytotoxic for the cells with the induction of the autophagic pathway. Trypan blue exclusion assay showed that 4-NC was cytotoxic in a dose-dependent manner for A172 and T98G cell lines. IC10 and IC50 values were at 32 µM and 41 µM for A172 and T98G respectively. Inhibition of cell proliferation was observed by total cell counts and by cell cycle analysis by flow cytometry, with cell cycle arrest of A172 and T98G cell lines respectively in the G1/G0 and S phases of the cell cycle. 4-NC induced up-regulation of autophagic pathways, as shown by immunoblotting for LC3-I/II, Real-Time PCR for ATG-7 and Beclin-1 genes, and by fluorescence microscopy observation of autophagic vacuoles in cells transfected with GFP-LC3 and electron microscopy. Glioma cells concomitantly treated with 4-NC and 3-MA, an inhibitor of the autophagic process, are more sensible to cell death, suggesting that autophagy protects the cells from the action of 4-NC.